Development of Digital Learning Media Based on I Spring Suite 11 to Improve Students' Interest and Learning Outcomes in Economics Subjects at SMA Negeri 11 Malinau in the 2024/2025 Academic Year - Fresdiana Octavia Sarumaha; Sutirman Sutirman (FKIP, Universitas Palangka Raya, 2025)
This research focuses on the development of digital learning media based on I Spring Suite 11 to assess: 10 t he feasibility of the digital learning media based on I Spring Suite 11; 2) the improvement of student interest in learning Economics at SMA Negeri 11 Malinau; and 3) the improvement of student learning outcomes in Economics at SMA Negeri 11 Malinau.The research method used is research and development (R&D) through the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with quasi-experimental analysis. The subjects of the research were 10 students from grade X at SMA Negeri 11 Malinau. The instruments used in this study were questionnaires given to media experts, material experts, and teaching practitioners (Economics teachers) to validate the questionnaire instruments and student responses to the digital learning media using the same questionnaires and pretest-posttest learning outcome tests.The research findings are as follows: 1) The feasibility of the I Spring Suite 11-based digital learning media was evaluated by material experts with a score of 78%, categorized as